The advantages and disadvantages of quantitative methods in schoolscape research - Savela Timo (United Kingdom, 2022)
This article focuses on the application of quantitative methods in schoolscape research, including a discussion of its advantages and disadvantages. This article seeks to rehabilitate the quantitative by re-theorizing the landscape in linguistic landscape (LL), moving from an area based study of visible forms to a poststructuralist and postempiricist interpretative study of landscapes. The article discusses previous quantitative LL research and introduces a quantitative approach developed by the author during a data gathering and annotation of 6016 items. Quantitative methods can provide valuable insight to the ordering of reality and the materialized discourses. Furthermore, they can mitigate personal bias. They cannot provide in-depth understanding of the analyzed items due to the inherently reductive nature of classification. However, considering that the objects of inquiry are discourses, not the artifacts themselves, the issue is not paramount. Nevertheless, large scale data gathering and annotation is time consuming, which sets practical limitations to research.